UV Spectrophotometric Determination of Quetiapine and Zonisamide - Baby Sudha Lakshmi, P.; Vardhan, S.V.M.; Ramachandran, D.; Rambabu, C. (Asian Journal of Chemistry, 2010)
Simple and sensitive UV spectrophotometric methods have been developed for the determination of quetiapine as fumarate and zonisamide having absorption maximum at 254.7 and 238.12 nm, respectively. These methods are extended to pharmaceuticals formulations. There is no interference from any common pharmaceutical additives and diluents. The methods have been statistically evaluated and found to be precise and accurate.